Economic geography and economic development in Sub-Saharan Africa - E. Maarten Bosker; Harry Garretsen (Center for Economic Studies and ifo Institute (CESifo), 2008)
The physical or absolute geography of Sub-Saharan Africa (SSA) is often blamed for its poor economic performance. A country's location however not only determines its absolute geography, it also pins down its relative position on the globe vis-à-vis other countries. This paper assesses the importance of relative geography, and access to foreign markets in particular, in explaining the substantial income differences between SSA countries. We base our empirical analysis on a new economic geography model. We first construct a measure of each SSA country's market access based on bilateral trade flows and then assess the relevance of market access for economic development. In doing so, we explicitly distinguish between the importance of access to other SSA markets and to the rest of world respectively. We find that market access, and notably intra-SSA market access, has a significant positive effect on GDP per capita. This indicates that improving SSA market access (e.g. by investing in intra- SSA infrastructure or through increased SSA integration) will have substantial positive effects on its future economic development.
Keywords: O10; O19; O55; F1; 330; Sub Saharan Africa; economic development; Entwicklung; Neue ökonomische Geographie; Markteintritt; Handelsregionalismus; Sozialprodukt; Afrika südlich der Sahara